2002
DOI: 10.1074/jbc.m202490200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factors GATA4 and dHAND Physically Interact to Synergistically Activate Cardiac Gene Expression through a p300-dependent Mechanism

Abstract: An intricate array of heterogeneous transcription factors participate in programming tissue-specific gene expression through combinatorial interactions that are unique to a given cell-type. The zinc finger-containing transcription factor GATA4, which is widely expressed in mesodermal and endodermal derived tissues, is thought to regulate cardiac myocyte-specific gene expression through combinatorial interactions with other semi-restricted transcription factors such as myocyte enhancer factor 2, nuclear factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
138
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 63 publications
7
138
2
1
Order By: Relevance
“…In addition, GATA4 is subjected to the lysine modifications via acetylation and sumoylation (10,11). Indeed, the transcriptional co-activator p300 interacts with GATA4 and enhances its transcriptional activity by acetylating lysine residues in the C-terminal region (35,36). Furthermore, cardiac overexpression of intact p300 has been shown to induce acetylation of GATA4 and cardiac hypertrophy and promote left ventricular remodeling after myocardial infarction in vivo (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GATA4 is subjected to the lysine modifications via acetylation and sumoylation (10,11). Indeed, the transcriptional co-activator p300 interacts with GATA4 and enhances its transcriptional activity by acetylating lysine residues in the C-terminal region (35,36). Furthermore, cardiac overexpression of intact p300 has been shown to induce acetylation of GATA4 and cardiac hypertrophy and promote left ventricular remodeling after myocardial infarction in vivo (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was proposed that a larger enhanceosome complex mediates the cardiac-specific expression, where several transcription factors like GATA4, SRF, MEF-2, NFAT, and HAND2, interact with each other through indirect mechanisms that involve transcriptional scaffolding molecules. The co-activator p300/CBP has been proposed as one of the molecules involved in the formation of the cardiacspecific enhanceosome (29,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…MyoD-E12 associates with myocyte enhancer factor-2A, a member of the MADS family, to activate myogenesis, but only one of these factors (either myocyte enhancer factor-2A or the MyoD-E12 complex) needs to interact with the DNA to activate transcription (3). dHAND has been shown to associate with the bHLH proteins E12 (6) and eHAND (18) and GATA4 and p300 (19); and the cardiospecific enhancer adenylosuccinate synthetase was the first target gene for dHAND (20). However, all of these studies demonstrated the dependence of dHAND binding to E-boxes within the promoter region to activate gene expression.…”
mentioning
confidence: 90%
“…6B), we believe that dHAND and Arix directly interact at the DBH promoter region to cooperatively activate transcription. Recently, dHAND has been shown to make direct contacts with the HD protein Nkx2.5 (26) and GATA4 and p300 (19); and together, these factors are able to activate transcription of the atrial naturetic peptide promoter. However, the interaction between GATA4 and dHAND does not alter either the magnitude or the pattern of DNA binding of either protein (19).…”
Section: Dhand Interacts Independent Of Dna Bindingmentioning
confidence: 99%
See 1 more Smart Citation